The use of social media for engineering lecturers and students - Shobirin, Achmad; Candra Leastari, Dian; Nuzula, Fidausi; Umeidah, Fitri (Bulletin of Social Informatics Theory and Application, 2018)
Social media provides convenience to the public in various aspects of life, one of which is ease of communication. Social media within the scope of education can be used as a medium of communication and information exchange between students and lecturers. This research purpose to determine the level of acceptance of social media use by lecturers and students. The data collection technique uses the Likert Scale survey method that refers to the TAM (Technology Acceptance Model). The results obtained from the research were respondents from lecturers (n = 3) and students (n = 56) in the Faculty of Engineering. The results of the research indicate that the use of social media has a positive influence on students and lecturers in the field of education.